Al Qur’an, Hadist, Dan Ijtihad Sebagai Sumber Pendidikan Islam - Rohadi, Rohadi; Roza, Ellya (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of this research is the Qur'an, Hadith, and Ijtihad as sources of Islamic education. This type of research is a library study. Data collection with documentation. Data analysis with SLR. The research results Al-Qur'an, Hadith, and ijtihad are the main pillars in the Islamic education system. The Qur'an serves as the main source of law and life guidance for Muslims, providing comprehensive moral and spiritual guidance. Hadith, which is a collection of sayings, actions and agreements of the Prophet Muhammad SAW, complements and explains the teachings of the Qur'an, providing concrete examples of the application of Islamic values ​​in everyday life. Meanwhile, ijtihad, namely the sincere efforts of ulama to interpret Islamic law based on the Al-Qur'an and Hadith, ensures the relevance of Islamic teachings to the times and the ever-changing social context. The combination of these three sources forms a strong and dynamic foundation for Islamic education, ensuring that its teachings remain contextual, applicable and sustainable.